The ionosphere : IGY instruction manual - Beynon, W. J. G.; Brown, G. M. (Annals of the International Geophysical Year, 1957)
Annals of the International Geophysical Year, Volume III: The Ionosphere covers the main branches of ionospheric research, particularly the vertical-incidence sounding technique. This volume is composed of seven chapters and begins with an introduction to the basic technique of pulse-sounding for most ionospheric studies. The next chapters describe the elementary theory basic to the understanding of ionospheric soundings and their physical interpretation. This topic is followed by examination of the basic principles, antenna systems, and photographic processing of sounding equipment. Other cha.